Uterine Rotation: A Cause of Intestinal Obstruction - Ernesto González-Mesa; Isidoro Narbona; Isaac Cohen; Emilia Villegas; Celia Cuenca (Case Reports in Obstetrics and Gynecology)
Intestinal obstruction is an uncommon surgical emergency during pregnancy that affects seriously the prognosis of gestation. The underlying cause can be identified in the majority of cases and usually consists of adhesions secondary to previous abdominal or pelvic surgery, followed in order of frequency by intestinal volvuli. In recent years there have been no reports in which the gravid uterus has been the cause of intestinal obstruction. We report the case of a woman in week 33 + 4 of pregnancy who developed extrinsic compression of the colon secondary to uterine rotation and pelvic impaction of the head of the fetus.